AKIBAT PERPISAHAN KEDUA ORANG TUA YANG DISEBABKAN PERSELINGKUHAN - Herlina Hanum Harahap (Jurnal Hukum Kaidah: Media Komunikasi dan Informasi Hukum dan Masyarakat, 2021)
It is natural that two human beings of different sexes, a man and a woman will be attracted to each other to form a life together in the household with the aim of forming a happy, peaceful, and prosperous family. However, human hopes cannot always be fulfilled as what they aspire to as that hope is only a mere hope without being able to be realized into reality. In the Law No. 1 of 1974 provides an understanding of marriage. Article 1 states that marriage is an inner and outer bond between a man and a woman as husband and wife, with the aim of forming a happy and eternal family (household) based on the Belief in the one and only God. Keywords: Divorce, Infidelity